The Impact of Exchange Rates and Net Operating Margin on Murabaha Financing in Islamic Commercial Banks in Indonesia Period 2019-2022 - Baso Akib; Fitriani, Fitriani; Nurul Haeriyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to investigate the impact of exchange rates and net operating margins on murabaha financing at Islamic Commercial Bank (BUS) companies in Indonesia during the 2019-2022 period. The research method used is descriptive quantitative with an associative approach. The research data were obtained from the financial statements of murabaha financing at BUS companies in Indonesia for the four years. The research sample consists of 48 monthly financial reports selected saturated from time series data. The data collection process was carried out through observation and documentation of available financial reports. The collected data were then analyzed using multiple linear regression analysis with the help of IBM SPSS 20 software. The results showed that partially, the exchange rate has a positive and significant influence on murabaha financing. This means that when the exchange rate strengthens, murabaha financing in BUS companies tends to increase. Conversely, the net operating margin has a negative and significant effect on murabaha financing, which means that the higher the net operating margin, the murabaha financing tends to decrease. Simultaneously, the exchange rate and net operating margin have a significant effect on murabaha financing.